Forbidden fruit : sex & religion in the lives of American teenagers - Regnerus, Mark (Oxford University Press, 2007)
'Forbidden Fruit' tells the definitive story of the sexual values and practices of American teenagers, paying particular attention to how participating in organised religion shapes sexual decision-making.